Peningkatan Hasil Belajar Matematika melalui Metode Penemuan Terbimbing dengan Setting Kooperatif - Rustiani S; Hafsyah Hafsyah; Suarti Djafar; Pratiwi Pujilestari Alam; Dian Firdiani (Departement of Mathematics Education, 2023)
This research is a class action research (Classroom Action Research) which aims to improve students' mathematics learning outcomes through the guided discovery method with a cooperative setting. The subjects of this study were students of class IX at MTSSMuhammadiyah Enrekang. This research was conducted in two cycles, each of which had three learning process meetings and one meeting where the learning outcomes test was conducted. The data collection technique used in this research is data on learning outcomes taken by giving tests at the end of each cycle, while data on teacher activities and student activities are taken using observation sheets during the learning process in the classroom. Based on the results of research and discussion for two cycles, it can be concluded that students' mathematics learning outcomes have increased from cycle I to cycle II. These conclusions were obtained from: (1) The average increase in students' mathematics learning outcomes from cycle I was 68.11 to cycle II of 83.11. (2) The students' mathematics learning mastery increased from cycle I to cycle II, namely from 22 students increased to 35 students, and classically achieved 100% completeness. (3) Increased student activity in participating in learning from cycle I to cycle II.